Signal timing manual - Urbanik, T. 1946- (Report (National Cooperative Highway Research Program) ;, 2015)
"TRB's National Cooperative Highway Research Program (NCHRP) Report 812: Signal Timing Manual - Second Edition, covers fundamentals and advanced concepts related to signal timing. The report addresses ways to develop a signal timing program based on the operating environment, users, user priorities by movement, and local operational objectives. Advanced concepts covered in the report include the systems engineering process, adaptive signal control, preferential vehicle treatments, and timing strategies for over-saturated conditions, special events, and inclement weather. An overview PowerPoint presentation accompanies the report."--